MAIN ACHIEVEMENTS OF THE SOUNDING ROCKET FLIGHT EXPERIMENT ATEK - Gülhan, Ali; Klingenberg, Florian; Siebe, Frank (2021)
The ATEK flight experiment was successfully launched on 13th July 2019 from the launch site Esrange in Kiruna and provided valuable flight data. The second stage and the payload reached an apogee of approx. 240 km. The second stage continued the descent on a ballistic trajectory and landed approx. 500 seconds after the take-off at a distance of approx. 67 km from the launch site. The payload was decelerated in the late subsonic flight phase using a two-stage parachute system to avoid a hard impact on ground and touched down after approx. 800 seconds flight time. The Health Monitoring System allowed the measurement of aerothermal and mechanical loads on the hybrid payload structure, motor adapter, motor case, tailcan and fins along the complete flight. Part of the data has been transmitted during flight to ground via telemetry at a low sampling rate of several Hertz. In addition, several impact-resistant data acquisition units could acquire the data at a high sampling rate up to one Kilohertz and stored it onboard. The hybrid payload structure and health monitoring data acquisition units have been recovered after the flight and showed complete functionality